Pengaruh Komite Audit dan Managerial Entrenchment terhadap Agresivitas Pajak serta Implikasinya terhadap Kinerja Keuangan Perusahaan - Andika Noviawan, Lalu; Handajani, Lilik; Ardana Putra, I Nyoman Nugraha (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p12, 2020)
This study aims to analyze the relationship between the audit committee and managerial entrenchment on tax aggressiveness and its implications for the company’s financial performance. A total of 71 manufacturing companies on the Indonesian Stock Exchange during the 2015-2017 periode were research samples. The results of data analysis using Partial Least Square show that managerial entrenchment and tax aggressiveness have a significant negative effect on financial performance. Managerial entrenchment reduces the company’s demand for monitoring of managers which results in a decrease in financial performance. Meanwhile, tax aggressiveness can cover managers’ rent extraction actions that impact on declining financial performance. Keywords: Audit Committee; Managerial Entrenchment; Tax Aggressiveness; Financial Performance.